Improving Learning Interest and Outcomes through Project-Based Learning with Digital Comics in Senior High School - Winda Rammayani; Erianjoni (Didaktika: Jurnal Kependidikan, 2025)
In the learning process, interest plays a very important role because it reflects a strong desire and motivation to engage in an activity. Interest influences a person's willingness to learn and actively participate in educational activities. This study aims to examine the application of the Project-Based Learning (PBL) model combined with digital comic media in class X Phase E at SMA Negeri 2 Rangsang, focusing on its impact on students' interest and learning outcomes. To increase students' enthusiasm for learning sociology, this classroom action research applies PBL by involving students in the creation of digital comics. The research design used is Participatory Classroom Action Research, where the researcher is actively involved throughout the process, from planning to data collection, analysis, and reporting. This study uses comprehension tests, observation sheets, and interviews to collect data, which is then analyzed descriptively to measure the effectiveness of learning. The results of the study indicate that students' initial interest in learning was below the expected standard. However, the implementation of PBL using digital comic media successfully increased both interest and learning outcomes. In the first cycle, the average learning outcome increased by 50%, and in the second cycle, it reached 80%. Additionally, students demonstrated greater engagement and enthusiasm, indicating that the learning process became more enjoyable.